PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA APOTEK AL AFIAH MANGARAN SITUBONDO - Alfaini, Diana; Ediyanto, Ediyanto; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is the process of identifying, creating and communicating value, and maintaining satisfying customer relationships to maximize company profits. Does location have a significant effect on consumer satisfaction? The population of this study used a purposive sampling method by distributing questionnaires to consumers who had visited the Al Afiah Mangaran Pharmacy. The purpose of this study is to determine the data analysis and hypothesis testing in this study using the Structural Equation Model - Partial Least Square (PLS-SEM). Based on the hypothesis test using the smart PLS 3.0 application, it shows that the location has a significant positive effect on consumer satisfaction. Service quality has a positive but not significant effect on consumer satisfaction. Location has a significant positive effect on repurchase intention. Service quality has a negative but not significant effect on repurchase intention. Consumer satisfaction has a significant positive effect on repurchase intention. Location on repurchase intention through consumer satisfaction has a positive but not significant effect. Service quality on repurchase intention through consumer satisfaction has a significant positive effect.